Implementation Of Istighatsah Routine Activities In Fostering Character Education Values Of Madrasah Aliyah Students - Damayanti, Alfina; Moh. Sahlan; Mustajab; Abd. Muhith (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Character education is essential in shaping students’ behavior and values. Schools play a vital role in instilling these values through structured activities, such as the routine Friday istighosah at MA Baniy Kholiel, which is expected to develop students’ character.This study aims to analyze the implementation of Friday istighosah activities in fostering the values of discipline and responsibility among MA Baniy Kholiel students. This qualitative study employed a case study design. Data were collected from four key informants: the school principal, teachers, students, and alumni of MA Baniy Kholiel. Data collection methods included observation of the istighosah activities, in-depth interviews with informants, and documentation review of relevant school records. Data analysis consisted of data reduction by focusing on relevant information, data display by organizing data into categories of discipline and responsibility, and verification through triangulation across sources to ensure validity. The findings reveal that routine Friday istighosah activities effectively foster the values of discipline and responsibility. Students exhibited punctuality and adherence to schedules, indicating internalized discipline. Additionally, habituation of participation in these activities increased students’ sense of responsibility, as they actively engaged and completed the activities conscientiously. Routine Friday istighosah activities at MA Baniy Kholiel play a significant role in developing students’ discipline and responsibility, highlighting the potential of habitual religious activities to support character education in schools.